Clinical immunological aspects of tick-borne encephalitis - I. N. Udintseva; O. Ye. Chechina; N. G. Zhoukova; L. V. Lukashova; N. V. Ryazantseva; A. M. Poponina; L. A. Malysheva; N. N. Bartfeld; S. A. Pershina (Бюллетень сибирской медицины)
In this article results of the clinical-immunological analysis with different forms tick-borne encephalitis of Tomsk Region during the period from 2000 to 2008 are represented. The revealled disbalance of cytokines alongside with breach of the expressions cytokines's receptor by limphocytes's cells, can be one of the main of the reasons to inefficiency answer when introducing the infectious agent in organism and shaping the chronic form to infectious pathology, in particular, with long presence of the antigen of the virus tick-borne encephalitis in blood. The trend to increase the level sick with long presence of the antigen of the virus tick-borne encephalitis in blood, with prevalence of the persons feminine flap, mainly average and senior age for the last years is given.